Dana Desa dalam Kebijakan Pemberdayaan Masyarakat Di Desa Sukosari Kecamatan Sukowono - Basilius Kaikimbinop; Itok Wicaksono (Empat Sembilan Publisher, 2024)
Sukosari Village, located in Sukowono Sub-district, Jember Regency, East Java Province, has an area of 531.888 hectares with the majority of the population working as farmers. Despite its great potential, the socioeconomic condition of the village community is still relatively low compared to the average of Jember Regency. This study aims to analyze the implementation of village funds in community empowerment efforts in Sukosari Village. The main focus lies on improving access to education and health services as an effort to improve the quality of life and human resources. The results show that the implementation of village funds in Sukosari village faces various challenges, including aspects of management, human resources and infrastructure. Good management of village funds is essential to ensure the effectiveness of programs designed for community welfare. In addition, the availability of qualified human resources and adequate infrastructure also determine the success of this program. To improve community welfare, several improvement measures are recommended, including: the creation of economic empowerment programs, increased access to education through scholarship programs, and improved health services through mobile health center programs and the expansion of health infrastructure. With these measures, it is hoped that Sukosari Village can achieve more equitable and sustainable welfare. The study concludes that despite the complex challenges, with effective management of village funds and improved human resources and infrastructure, Sukosari Village has great potential to improve its socioeconomic conditions. Proper implementation will pave the way for village progress, making Sukosari Village an example for other villages in optimizing village funds for community empowerment and sustainable development. Translated with DeepL.com (free version)